EFEKTIFITAS PEMBELAJARAN DENGAN MEDIA UNTUK PERBAIKAN HASIL LOMPAT JAUH - Daulay, Dicky Edwar; Priono, Joko; Natas Pasaribu, Ahmad Muchlisin (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2020)
The purpose of this research was to find out the extent of improvement in the jumps and the results of the jumps by using various forms of media at the High School Student Athletics Club 2 Range in 2020. This study was students who were still in class X who were sampled with a total of 35 students. action will be given in the form of learning using a variety of media to the results of improvement of the results of the jump. The method used in this research is classroom action research. The location of this research is in SMA Negeri 2 Kisaran Asahan Regency where the school has a very active Athletic club. This research was conducted in February 2020. To obtain data in this study, a test of learning outcomes was carried out at the end of each cycle in the form of the application of the basic jump assessment technique. With the implementation of this research study test results carried out for two weeks or two meetings. Data analysis was performed by data reduction and data exposure. The results of the study concluded: (1) from the test of learning outcomes obtained as many as 30 students with grades after being confirmed (69.04%) had reached the level of mastery learning while 5 students (30.96%) had not reached the level of mastery learning. From this study, it can be concluded that the use of media can be an improvement in the results of the long jump so that its effectiveness is very precise. This research is designed so that the teacher or trainer is able to be a solution to improve the results of the long jump for the students or athletes he trains.